Kompleksowe postepowanie leczenicze nowotowrów gruczołu sutkowego = Comprehensive therapeutic treatments methods of mammary gland carcinoma - Mieszkowski, Jan Paweł; Pastwik, Magdalena; Stejbach, Karolina; Przybyłowicz, Magdalena; Pijankowska, Edyta (Journal of Education, Health and Sport, 2015)
Mieszkowski Jan, Pastwik Magdalena, Stejbach Karolina, Przybyłowicz Magdalena, Pijankowska Edyta. Kompleksowe postepowanie leczenicze nowotowrów gruczołu sutkowego = Comprehensive therapeutic treatments methods of mammary gland carcinoma. Journal of Education, Health and Sport. 2015;5(7):314-342. ISSN 2391-8306. DOI 10.5281/zenodo.20068 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A314-342 https://pbn.nauka.gov.pl/works/585127 http://dx.doi.org/10.5281/zenodo.20068 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2015. Revised 05.07.2015. Accepted: 12.07.2015. KOMPLEKSOWE POSTEPOWANIE LECZENICZE NOWOTOWRÓW GRUCZOŁU SUTKOWEGO Comprehensive therapeutic treatments methods of mammary gland carcinoma Mieszkowski Jan1, Pastwik Magdalena2, Stejbach Karolina2, Przybyłowicz Magdalena2, Pijankowska Edyta2 1. Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska 2. Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy Autor do korespondencji: mgr farm. Jan Mieszkowski e-mail mieszkowskijan@gmail.com Słowa kluczowe: gruczoł sutkowy, kancerogeneza, mammografia, chemioterapia, mastektomia. Key words: mammary gland, carcinogenesis, mammography, chemotherapy, mastectomy. Streszczenie: Nowotwory piersi są obecnie najczęściej diagnozowanym nowotworem wśród kobiet na świecie, z liczbą nowo zdiagnozowanych zachorowań w 2012 roku na poziomie 1 670 000 pacjentek. Wśród zgonów z powodu chorób nowotworowych, nowotwór piersi jest pierwszą, w krajach mniej rozwiniętych i drugą (po nowotworach płuc) w krajach rozwiniętych przyczyną zgonów kobiet. W Polsce obserwuje się ciągły wzrost zachorowań na nowotwory piersi. Najczęściej nowotwory piersi wykrywane są u kobiet w wieku 50 - 69 lat, jednak ostatnio obserwowany jest wyraźny wzrost zachorowań u kobiet młodszych. W ostatnim dwudziestoleciu nowe strategie profilaktyczne pozwalają na wykrywanie rozwoju choroby we wczesnym jej stadium, zwiększając znacząco szansę pacjentek na dłuższe życie lub wyzdrowienie. Niezmiennie jednak leczenie nowotworów piersi pozostaje procesem długotrwałym i nie dającym gwarancji na zahamowanie rozwoju zmian chorobowych i wyzdrowienie. Skuteczność terapeutyczna stosowanych metod leczenia jest bardzo zróżnicowana i wymaga każdorazowo indywidualizacji, oraz zastosowania odrębnych strategii leczenia (chirurgia, farmakoterapia, fizjoterapia, psychoterapia), które pozwolą na poprawę ogólnego stanu zdrowia chorego, spowolnienie progresji choroby lub poprawę komfortu życia. Niniejszy artykuł jest próbą usystematyzowania dostępnych metod diagnostyki i terapii nowotworów piersi ze szczególnym skupieniem się na kompleksowym podejściem do problemu klinicznego jakim są nowotwory piersi. Ma to na celu lepszego zrozumienie roli wczesnej diagnostyki w przeciwdziałaniu rozwojowi nowotworów piersi oraz konieczności prowadzenia kompleksowych działań leczniczych (współdziałania metod leczenia z zakresu farmacji, fizjoterapii, psychologii) w terapii tego schorzenia. Summary Breast cancers are now the most commonly diagnosed cancer amongst worldwide women, with the number of newly diagnosed cases 1 670 000 patients (in 2012). Among deaths due to cancer, breast cancer is the first cause of women death in less developed countries and the second (after lung cancer) in developed countries. In Poland continuous increase of breast cancer incidences is being observed. Breast cancers are mostly diagnosed in 50 - 69 years women, but recently the number of breast cancer rates in younger women is increasing. In the last two decades, new prevention strategies allow the detection of the disease development in its early stages, significantly increasing the chance of patients longer life or full recovery. However, the treatment of breast cancer remains a long-term process which not gives a guarantee for the inhibition and recovery. The therapeutic efficacy of therapy methods is very diverse and always requires customization, and uses separate treatment strategies (surgery, pharmacotherapy, physiotherapy, psychotherapy), which will improve patient general health, slowing down the disease progression or improving the quality of life. This article is an attempt to systematize the available diagnosis and treatment methods of breast cancer with a particular focus on a comprehensive approach to this clinical problem. The aim is to better understand the role of early diagnosis in prevention of breast cancer development and the need of a comprehensive approach (interaction of treatments methods in the field of pharmacy, physiotherapy, psychology) in the treatment of this disease.